Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa - Kluge, Nikita J. (Zootaxa, 2020)
Larvae, subimagines, imagines of both sexes and eggs of Demoulinia crassi (Demoulin 1971) are described based on reared specimens from South Africa. Newly revealed characters testify that Demoulinia Gillies 1990 belongs to the plesiomorphon Protopatellata. Demoulinia includes two species, the South African species D. crassi and the Madagascar species D. insularis Lugo-Ortiz & McCafferty 1998 (= D. assimilis Gattolliat 2003 syn. n.). Larvae of these two species differ in structure of claws and paraprocts; imagines and eggs are described for D. crassi only. Larvae of two unnamed species of Protopatellata from South Africa are briefly described and figured; possibly, one of them belongs to africanum [Cloeon], which is the type species Austrocloeon Barnard 1932.